Sabores e identidades na Feira da Lua : um estudo etnográfico da comida de feira - Costa Neto, Izaltino Rodrigues da (2023)
The theme of this research is dedicated to ethnographically observe the Feira da Lua, held in Aragarças/GO. From the experiences and situations related to gastronomy and trade food, it was sought to understand how relations of identity, sociability, belonging, among other links could be constituted in the context in question.The study is based on analyzes of participant observation carried out between September 2021 and April 2022, aiming to explore and present the most significant relationships permeated by the food that transits through Feira da Lua. The investigation of this empirical field took place in the itinerances between Anthropology and Gastronomy, highlighting or confronting the conventions that attest to identities, belongings or bonds that food creates between subjects, groups and places.